Brigatisti sulla Carta: Il Racconto delle Br Oltre la Non Fiction - Marzi, Marco (Italogramma, 2025)
This article explores the intersections between autobiographical and fictional writing in works connected to the so-called "Brigatist literature." Beginning with Compagna luna by Barbara Balzerani and Armi e bagagli by Enrico Fenzi, which can be read as autobiographies disguised as novels. It then moves to Princesa, a novel that conceals an autobiographical core. Finally the analysis shifts to contemporary Italian fiction, focusing on Il tempo materiale by Giorgio Vasta and La ricreazione è finita by Dario Ferrari, where the brigatist milieu is reimagined through a parodic and farcical lens.